2020
DOI: 10.1155/2020/8835824
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life in Chronic Liver Failure Patients Measured by OHIP-14 and GOHAI

Abstract: Background. Oro-dental diseases are prevalent in chronic liver failure (CLF) patients. The aim of this study was to evaluate the quality of life associated with oral health in candidates for liver transplant surgery. Materials and Methods. The demographic information of 105 end-stage liver cirrhotic patients was collected. All patients were ordered a panoramic view for pretransplant dental evaluation. The DMFT (decayed-missing-filled tooth) index was calculated for dental examination. The model for end-stage l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
4
1
1
Order By: Relevance
“…Since both age groups were considered in the present study, it seems that this index is higher than that in the general population of Iran, which consistent with the findings by Helenius-Hietala et al [15]. In the of Zahed et al [24], the DMFT index and bone level were not significantly different between the two groups (patients with chronic liver failure versus healthy individuals).…”
Section: Resultssupporting
confidence: 91%
“…Since both age groups were considered in the present study, it seems that this index is higher than that in the general population of Iran, which consistent with the findings by Helenius-Hietala et al [15]. In the of Zahed et al [24], the DMFT index and bone level were not significantly different between the two groups (patients with chronic liver failure versus healthy individuals).…”
Section: Resultssupporting
confidence: 91%
“…A total of 771 articles were selected for reading by title and abstract, of which 752 were removed for not meeting the eligibility criteria based only on the initial screening. A total of 19 articles 5 , 9 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 were read in their entirety. Of these, 16 were excluded because two 18 , 19 evaluated oral findings/characteristics in adults; five 23 , 26 , 28 , 29 reported oral features/findings/characteristics of post liver transplantation; three 9 , 16 , 28 presented merged data of oral characteristics/findings between pre- and post-transplantation phases (which made it impossible to extract data only from the pre-transplantation phase); two 10 , 27 evaluated oral conditions in two groups, liver and kidney diseases; one 16 was a literature review; and three 21 , 22 , 24 were excluded since the archives were not found.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 articles 5 , 9 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 were read in their entirety. Of these, 16 were excluded because two 18 , 19 evaluated oral findings/characteristics in adults; five 23 , 26 , 28 , 29 reported oral features/findings/characteristics of post liver transplantation; three 9 , 16 , 28 presented merged data of oral characteristics/findings between pre- and post-transplantation phases (which made it impossible to extract data only from the pre-transplantation phase); two 10 , 27 evaluated oral conditions in two groups, liver and kidney diseases; one 16 was a literature review; and three 21 , 22 , 24 were excluded since the archives were not found. Later, two additional articles 31 , 32 were identified through manual search of the reference lists and were fully read, but were not included once they did not meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Entre os 19 estudos incluídos, 11 avaliaram apenas portadores de cirrose hepática avançada e candidatos a transplante de fígado (Kwak et al, 2020), (Zahed, Ranjbar, et al, 2020), (Grønkjaer et al, 2018), (Lins et al, 2017), (Wu et al, 2021), (Hicks, 2015), (Helenius-Hietala et al, 2012), (Grønkjaer et al, 2021), (Lins et al, 2011), (Pidhorodeckyj et al, 2018), (Ramaglia et al, 2019), seis avaliaram grupo pré transplante e controles sadios (Zahed, Bahador, et al, 2020), (di Profio et al, 2018, (Ghapanchi et al, 2019), (Ghapanchi et al, 2020), (Sérgio et al, 2012, (Castellanos-Cosano et al, 2013), um estudo avaliou participantes no pré e pós transplante em comparação com grupo controle saudável (Schmalz et al, 2018), outro comparou pacientes do prétransplante com os do pós-transplante (Kauffels et al, 2017).…”
Section: Resultsunclassified